2005
DOI: 10.1002/fuce.200400068
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Pressurised Hybrid Systems Based on Integrated Planar Solid Oxide Fuel Cell (IP‐SOFC) Technology

Abstract: This work describes different models, developed by the Thermochemical Power Group at the University of Genoa (Italy), for the simulation of solid oxide fuel cell and gas turbine hybrid systems. The paper focuses on both “cores” of the system: the fuel cell stack on the one hand and the turbomachinery and the auxiliaries on the other hand. Therefore, in the first part of the paper the models developed for the analysis of the Rolls‐Royce Integrated Planar SOFC cells are presented; the results are compared to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Operating conditions (typically 10-20 bar p(H 2 O)) are the must. The use of high water pressure by industrialists allows an increased efficiency and in consequence decreasing of hydrogen production/conversion cost [22][23][24][25][26][27]. Our previous studies, performed in a strict collaboration with Industrial partner, showed however that high water pressure can significantly accelerate a material ageing [20].…”
Section: Introductionmentioning
confidence: 99%
“…Operating conditions (typically 10-20 bar p(H 2 O)) are the must. The use of high water pressure by industrialists allows an increased efficiency and in consequence decreasing of hydrogen production/conversion cost [22][23][24][25][26][27]. Our previous studies, performed in a strict collaboration with Industrial partner, showed however that high water pressure can significantly accelerate a material ageing [20].…”
Section: Introductionmentioning
confidence: 99%
“…Models that simulate only the anode (Suwanwarangkul et al, 2003;Yakabe et al, 2000Yakabe et al, , 2004Costamagna et al, 1998) or the cathode Svensson et al, 1996;Chen et al, 2004), a single SOFC cell (Zhu et al, 2005;Zhu and Kee, 2003;Achenbach, 1994;Inui et al, 2006;Iwata et al, 2000;Ji et al, 2006) or a whole stack (Recknagle et al, 2003;Petruzzi et al, 2003;Chan and Ding, 2005;Burt et al, 2004) have been reported. Additionally, both steady state (Aguiar et al, 2002(Aguiar et al, , 2004 and dynamic models (Iora et al, 2005;Achenbach, 1995;Xue et al, 2004Xue et al, , 2005Petruzzi et al, 2003;Aguiar et al, 2005;Magistri et al, 2005) have been developed. Several reported models have been constructed using programming languages (Fortran, C++ or MATLAB) while others use commercial simulation packages, (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date only a few SOFC-GT hybrid systems have been built and operated in demonstrations by companies such as Siemens [3], Mitsubishi Heavy Industry [4] and Rolls Royce [5]. Nevertheless, theoretical studies have been widely undertaken and results are available in the literature, involving the thermodynamic analysis, design and performance modelling of SOFC-GT hybrids through individual and collaborative efforts [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%